2020
DOI: 10.1007/s11604-020-00948-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pneumonia: infection control protocol inside computed tomography suites

Abstract: A novel coronavirus (severe acute respiratory syndrome coronavirus 2) causes a cluster of pneumonia cases in Wuhan, China. It spread rapidly and globally. CT imaging is helpful for the evaluation of the novel coronavirus disease 2019 (COVID-19) pneumonia. Infection control inside the CT suites is also important to prevent hospital-related transmission of COVID-19. We present our experience with infection control protocol for COVID-19 inside the CT suites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 3 publications
0
62
0
5
Order By: Relevance
“…This is because we need to use the CT suites for the next patients as soon as possible. Nakajima et al reported that CT examinations on the patients with COVID-19 confirmed or suspected were performed at the end of the daily CT schedule [1]. Therefore, we estimate that their interval time may be approximately less than 12-18 h from scanning the patients with COVID-19 infection confirmed or suspected to scanning the next patient.…”
Section: To the Editormentioning
confidence: 96%
See 3 more Smart Citations
“…This is because we need to use the CT suites for the next patients as soon as possible. Nakajima et al reported that CT examinations on the patients with COVID-19 confirmed or suspected were performed at the end of the daily CT schedule [1]. Therefore, we estimate that their interval time may be approximately less than 12-18 h from scanning the patients with COVID-19 infection confirmed or suspected to scanning the next patient.…”
Section: To the Editormentioning
confidence: 96%
“…We read with great interest an article by Nakajima et al entitled "COVID-19 pneumonia: infection control protocol inside computed tomography suites" published in the Japanese Journal of Radiology [1]. Rapidly increasing are publications regarding the diagnosis of COVID-19 pneumonia by computed tomography (CT), but limited articles seemingly have reported infection control in the CT suites.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Nakajima et al noted that "CT imaging is helpful for the evaluation of the novel coronavirus disease 2019 (COVID-19) pneumonia. Infection control inside the CT suites is also important to prevent hospital-related transmission of COVID-19 [1]". The role of CT scan in diagnosis of COVID-19 is widely discussed.…”
Section: Dear Editormentioning
confidence: 99%